A Rare Case of Lumbar Traumatic Intradiscal Hematoma Followed by Repeatative Occupation Related Minor Trauma - Woo-Keun Kwon; Jong-Keon Oh; Taek-Hyun Kwon; Youn-Kwan Park; Hong Joo Moon; Joo-Han Kim (Journal of Trauma and Injury)
A case of surgically treated intervertebral disc extrusion with intraoperatively confirmed intradiscal hematoma in a 30-year-old physical trainer is presented. Preoperative magnetic resonance imaging revealed downward migrating disc herniation, without definite suggestive findings of intradiscal hematoma. Intervertebral disc herniation with concomitant intradiscal hematoma is extremely rare, but could occur in patients who have excessive axial stress to the spine occupationally. In our case, the patient was an occupational physical trainer who had repetitive minor trauma to the lumbar spine. Although the patient did not have any clear history of major trauma to the spine, the intraoperative findings revealed intradiscal hematoma, which is very rare. The presence of intradiscal hematoma is to be suspected even when preoperative imaging studies shows indefinite findings of hematoma, considering the change in signal intensity of hematoma by time.